Effect of maternal lactoferrin supplementation on iron contents and anti-oxidant capacity in Dahe black Pig neonates - Zhang, Chunyong; Li, Cenxi; Xing, Xiaokun; Ji, Peng; Li, Meiquan; Pan, Hongbin; Guo, Rongfu; An, Qingcong (Frontiers in Veterinary Science, 2022)
Iron levels are closely related to animals' growth performance and anti-oxidant function. Lactoferrin (LF) is an iron-binding glycoprotein, which can promote the absorption of iron and regulate the immune function. This study aimed to clarify the effect of maternal LF supplementation on the iron metabolism of Dahe piglets. Sixty sows (Dahe black, parity 3-4, no significant differences in body weight) were randomly assigned to five groups: control (basal diet with no iron supplementation), supplemented 100 (LF1 group), 200 (LF2 group) or 300 (LF3 group) mg LF/kg in basal diet, and a basal diet supplemented with 100 (Fe-Gly group) mg Fe/kg as ferrous glycine (Fe-Gly). The serum anti-oxidant parameters of the sows and neonatal piglets were determined. The iron contents, anti-oxidant gene expression levels, and Fe-acquisition genes were detected in the liver, heart, spleen, and other neonatal organs. The results indicated that 1) the LF3 group of sows had the highest serum and colostrum iron contents (P < 0.05). Adding LF and Fe-Gly to sow diet significantly reduced the iron content in heart, lung, duodenum and jejunum of newborn. 2) Maternal LF can increase serum glutathione peroxidase (GSH-Px) and total superoxide dismutase (T-SOD) activities of sows. Compared with other groups, the total anti-oxidant capacity (T-AOC) activity of LF2 groups increased significantly (P < 0.05). 3) LF significantly increased piglet serum GSH-Px, T-SOD and T-AOC activities (P < 0.05). 4) Gene expression levels of GSH-Px and SOD in the liver and duodenum of neonates are significantly reduced by LF or Fe-Gly (P < 0.05). 5) The expression levels of hepcidin and LF in the liver were increased by LF, while in the duodenum and jejunum, hepcidin expression was downregulated by LF and Fe-Gly (P < 0.05). In conclusion, maternal LF supplementation significantly improves iron absorption and increases iron storage in neonatal piglets, delivering superior anti-oxidant activity and preventing iron deficiency.